Political Will Government in Prevention of Post-Reform Corruption IN Indonesia - Rasyid , Fauzan Ali (International Journal of Psychosocial Rehabilitation, 2020)
This article focuses on discussing the political will of the government in preventing post-reform corruption in Indonesia. This study aims to see how the political will of the government in combating corruption. Methods applied by using a qualitative approach with descriptive purposes. Data collection was done purposively and documentation studies from various secondary sources. This research found that the government has political will reflected in policies to eradicate corruption in Indonesia. Government policies related to the political interests of political parties. The existence of party political interests can eventually be an obstacle to handling corruption. In addition to a plan, the government's political will in eradicating corruption also reflected in the formation of institutions/bodies that deal with crime. The existence of these institutions/bodies correlates with the political will of the government. The actors working in these institutions/agencies are representative of the government. This research concludes that in dealing with corruption, the government has political will through the issuance of policies that favor the rule of law and the institutions/agencies tasked with eradicating corruption.